Abnormal cytology in oropharyngeal brushings and in oral rinses is not associated with HPV infection: The OHMAR study. Issue 9 (2nd June 2020) - Benevolo, Maria; Rollo, Francesca; Giuliani, Massimo; Pichi, Barbara; Latini, Alessandra; Pellini, Raul; Vescio, Maria Fenicia; Morrone, Aldo; Cristaudo, Antonio; Donà, Maria Gabriella
Abstract : Background: No screening is available for human papillomavirus (HPV)‐associated oropharyngeal cancers. The authors investigated whether cytology may be used as a screening tool and whether oral HPV infection is associated with cytologic abnormalities detected in oropharyngeal brushings and in oral rinse‐and‐gargle specimens from asymptomatic individuals at increased risk for oral HPV infection. Methods: Specimens were collected from men who have sex with men at 6‐month intervals. Oropharyngeal samples and oral rinse‐and‐gargle specimens were collected using a cytobrush and mouthwash, respectively. Exfoliated cells were dispersed in PreservCyt. Liquid‐based slides were stained with Papanicolaou. An HPV genotyping test using a linear array was used for HPV detection. Associations with abnormal cytology were investigated using logistic regression. Results: Overall, 631 brushings and 802 rinses collected from 310 individuals were evaluated; of these specimens, 2 brushings (0.3%) and 10 rinses (1.2%) were inadequate for morphologic evaluation. Of the adequate samples, 35 of 629 brushings (5.5%) and 19 of 792 rinses (2.4%) were abnormal. No associations of high‐risk HPVs or HPV‐16 infection with cytologic abnormalities were observed for oropharyngeal brushings (high‐risk HPVs: odds ratio [OR], 1.19; 95% CI, 0.41‐3.50; P  = .75; HPV‐16: OR, 0.76; 95% CI, 0.10‐5.84; P  = .79) or for oral rinses (high‐risk HPVs: OR, 1.13; 95% CI, 0.26‐4.98; P  = .87; HPV‐16: OR, 0.62; 95% CI, 0.04‐10.60; P  = .74). Concurrent moderate/heavy drinking and smoking significantly increased the risk of cytologic abnormalities in the brushings (hazard ratio, 4.84; 95% CI, 1.15‐20.43; P  = .03). Conclusions: Oral HPV infection by high‐risk HPVs and HPV‐16 does not confer an increased risk of cytologic abnormalities in oropharyngeal brushings and oral rinses. Abnormal cytology seems to be associated with smoking and drinking habits. Abstract : Abnormal cytology on oropharyngeal brushings and oral rinse‐and‐gargles is not associated with infection by high‐risk human papillomaviruses or by human papillomavirus type 16. Smoking and drinking habits seem to increase the risk of cellular abnormalities.